Difference In Mothers' Knowledge of Balanced Nutrition For Preschool Children Before And After Receiving Nutrition Education Using Powerpoint Slides At biMBA AIUEO Unit Vila Bintaro Indah - Riskia, Rahmadina Mega; Marbun, Rosmida Magdalena (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2023)
Indonesia has a "Double Burden of Malnutrition". Based on Basic Health Research (Riskesdas) data for 2018, the prevalence of undernutrition is estimated at 13.8%, while the prevalence of overweight is reported to be at 8%. Balanced nutrition is crucial for normal growth, physical development, and cognitive abilities. The key to the success or failure of nutritional status in toddlers lies in the mother's knowledge regarding nutrition. Nutrition education is an effort to overcome nutritional problems by increasing mothers' knowledge. The purpose of this study is to examine the difference in mothers' knowledge of balanced nutrition for preschool children before and after receiving nutrition education using PowerPoint slides at biMBA AIUEO Unit Vila Bintaro Indah. The research method employed in this study was a pre-experimental design using a one-group pre-test-post-test approach.. The total population in this study is 80 individuals and a total of 31 mothers were included as participants taken utilized purposive sampling. Data was collected through a questionnaire (Google Form). Statistical analysis were conducted using the Paired Sample t-test. The results showed that there is a significant difference in the mother's knowledge regarding balanced nutrition for preschool children with p = 0.000 (p <0.05). The suggestion given is that the school encouraged to collaborate with the local Community Health Center (Puskesmas) to provide continuous nutrition education for preschool children.